(untitled) (Palíndromo, 2021)
This article is about the experiences that found the look, posture and gestures of two artist-researchers who take the book Água Viva, by Clarice Lispector, as a common poetic reference. With the attempt to reflect on certain provocations of this edition in relation to the artist’s critical self-portrait, the goal is to establish a dialogue between the different investigations on the figure of the artist today, which includes references, practices and plural artistic-theoretical discourses. The intention, here, is to give flux to thoughts that sometimes flow through academic-intellectual paths, sometimes through experiences and empiricisms, making themselves exist not only through the venous lines of the real region, but, as much or more, through the intricacies of the imaginary and imagination. By the mutual exercise of thought, passages by authors such as Bauman, Mondzain, Nancy, Blanchot and Arendt are articulated, in addition to mentions of Saramago, García Márquez, Mia Couto and Lispector herself, whose company motivates us to write in pair. After all, it is in the domains of reflection and inclusion that we work on sharing differences in the depth of the interlines.